PENETAPAN KADAR VITAMIN B1 PADA GENJER (LIMNOCHARIS FLAVA) DENGAN PENGUKUSAN MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Previta Zeisar Rahmawati; Dewi Cholimatus Sa'diyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
ABSTRACTGenjer (Limnocharis flava) is a daily consumable plant that often used as vegetable by wide society. It known have completed nutritional content such as protein, carbohydrate, mineral and vitamin. Genjer also known as good source of B1 vitamin. The purpose of this study was to identify B1 vitamin level of fresh and steamed genjer plant. Genjer plant were steamed for 2 minutes and 4 minutes. We also want to examine the best steamed time for the plant towards B1 vitamin level. Determination of genjer B1 vitamin level wa used UV-Vis Spectrofotometry at 511 nm, and thiamine was used as the standart solution. The study shown that B1 vitamin level were o,121 mg/100 g, 0,035 mg/100 g and 0,027 mg/100 g in fresh, 2 minutes steamed and 4 minutes steamed genjer plants respectively. We were done a quantitatively analysis of collected data to describe B1 vitamin level in treated genjer plants. The result showed that the longer of steamed period will reduce more of B1 vitamin level at genjer plants. We suggested that B1 vitamin more soluble in water and processing technique related with water have an effect towards B1 vitamin level, and 2 minutes steaming reduce less of B1 Vitamin compared to 4 minutes steaming. Keywords: Genjer (limnocharis flava), Analysis of Vitamin B1 Levels, UV-Vis Spectrophotometer